Application of GA for three-area power system after deregulation with valve position limit - Guolian Hou; Xinyan Zheng; Lina Qin; Jianhua Zhang (2012 24th Chinese Control and Decision Conference (CCDC), 2012)
In recent years, electric power industry has been moving towards a deregulated framework all over the world. Many problems have appeared in the new situation. The valve position limit exhibits nonlinear character in the deregulated environment. In this work, distribute companies participation matrix (DPM) is brought in to analyze the effect of the DPM to the dynamic performance of the system. T-S model is proposed to construct valve position nonlinear constraint. Real-coded GA is used and the initial population is obtained by uniform sampling. It takes less time than the common algorithm. The simulation results of the three-area power system are then introduced to demonstrate the validity of the results.